Al-Qâḍi Abu al-Hasan Ali bin 'Abd al-Aziz al-Jurjâni: Hâmil as-Salâm - Hilda Dimyati Asmara; Mukhamad Syaiful Milal; Ahmad Habibi Syahid (Alfaz (Arabic Literatures for Academic Zealots), 2021)
Ali Bin Abdul Aziz Al-Jurjani built his concept orientation as a way out of the problems of the world of classical Arabic literary criticism, so as to provide objectivity in criticizing a work. Abdul Aziz comments to all the poets of his time, quoting Al-qodhi's own words: "If a poet finds fault and then finds goodness in other poets then a poet will make excuses to accept it". It means the absurd contradiction between one poet and another. Abdul Aziz offers a duality perspective towards Al-Mutanabbi and his enemies. Ali Bin Abdul Aziz's perspective is stated in his book, Al-Washatah baina Mutanabbi wa Khusumihi. Ali Bin Abdul Aziz's critical opinion gives a start and a difference in the objective interpretation of problems in classical Arabic literary criticism. This study will uncover the form of neutrality of Ali Bin Abdul Aziz in the book Al-Washatah baina Mutanabbi wa Khusumihi, with a form of criticism as well as a symbol of the meaning of appreciation of literature.